An approach to the educational system of switzerland: curricula 21 and its implication in the sustainable human development - Rodriguez R. de Flückiger, Bony (2018)
The world societies go through a very rapid transformation like result, between other things, to the incorporation of the technologies to all the ambiences of the personal and social life. Switzerland as other countries is not foreign tothese changes and in the educational ambience, it offers across its Curricula 21 an alternative according to the current requirements. The education in Switzerland is a competence transferred in 26 Cantons that shape the Swiss Confederacy.Twenty-one Cantons of German speech received the Curricula 21 for the harmonization of the obligatory school in the frame of the interactional Concordat HarmoS. The target of the Concordat consists of improving the quality of theobligatory public education and overcoming the obstacles that make the educational mobility difficult between the cantons.